Orthodontic Postgraduate Students' Perception on Didactics and Clinical Training During the COVID-19 Crisis. Issue 3 (July 2021) - Arunachalam, Sivakumar; GVD, Harsha; Sharan, Jitendra; Ghandikota, Alekhya; Ram, RSVM Raghu; Praveen, Gadde
Objective: With the global crisis of the COVID-19 pandemic, orthodontic postgraduate students' education and clinical training might be affected. The objective of this study was to explore their perception on didactics and clinical training. Materials and Methods: A pretested and validated 26-item online survey that addressed COVID-19's impact on didactic components and clinical management was sent to postgraduate students in the Indian subcontinent. The survey was available for 3 days, and the responses were collected and analyzed. Results: Overall, 165 out of 244 (67.62%) orthodontic postgraduate students completed the survey. Of them, 88.48% noted that orthodontic education and patient management are at stake because of the ensuing crisis. The majority (66.28%) acknowledged that Internet-based education will become the significant part of postgraduate coursework. With regard to patient care, 80% felt that 2-way communication channels and a guarded approach with strict infection control protocols may be the way forward during the crisis. Many preferred attending patients with space closure stage at the follow-up (51.23%) and to postpone new case start-ups until normalcy returns. About 55% of the respondents felt that clear aligners could transform into a popular orthodontic practice regimen if the crisis continues. Conclusions: Orthodontic postgraduate students were concerned that the crisis would go on and affect their education. They perceived transition of face-to-face didactic learning and summative assessments to online settings as a viable approach during the COVID-19 crisis. They felt that orthodontic clinical training would benefit from teleorthodontic approaches and prioritization of care and its alignment with crowd control.